The impact of a standard pain assessment protocol on pain levels and consumption of analgesia among postoperative orthopaedic patients. (November 2021) - Gonzales, Analita; Mari, Mohammad; Alloubani, Aladeen; Abusiam, Khetam; Momani, Thaer; Akhu-Zaheya, Laila
Abstract: Background: Pain is a leading concern in post-surgical orthopaedic settings; andeffective pain assessment tools are important aspects of pain management. Objective: This study assessed the effect of using standard pain assessment protocols (SPAP) on pain levels, pain management, and analgesia consumption among patients in the first 24 h following orthopaedic surgery. Methods: In total, 101 patients were recruited and assigned to the comparison group (n = 50) and experimental group (n = 51). SPAP was used in the experimental group while the comparison group received routine care. Pain levels at rest and during movement and analgesic consumption were compared between the two groups. Findings: There were significant differences in pain levels between the comparison and experimental groups. The experimental group consumed significantly less pain medication at 8–11 h of opioid medications and 12–15 h of non-opioid medications ( P < .001). The use of non-pharmacological modalities was significantly higher in the experimental group compared to the comparison group ( P < .001). Conclusions: Regular pain assessment and management using SPAP can promote pain management and reduce pain levels as well as reduce analgesia administration and promote the use of non-pharmacologic approaches. These outcomes can result in fewer side effects for patients. Implications: The findings suggest that using SPAP can result in improved outcomes as well as the use of non-pharmacologic approaches to pain management. This approach can result in better outcomes and increased communication between the nurse and the patient.